Analisis Kebutuhan Pay Tv Transvision Daerah Dki Jakarta Dengan Servqual Dan Model Kano - Leo Cahya Trias Putra Rachman; Maria Dellarosawati Idawicasakti; Sari Wulandari (eProceedings of Engineering, 2015)
Abstract The trend of Pay TV and its penetration in Indonesia has the potential to continuously grow annually and attracts a bigger number of audience. The result of this trend is that the competition in the industry of Pay TV services has become more competitive every year. Pay TV is a service that broadcasts television channels for the audience who are willing to subscribe and pay frequently. Transvision is one of the providers of Pay TV service in Indonesia, and has to have the power to compete in this industry. The approach to the solution of this problem is to identify and classify the attributes of needs based on SERVQUAL and Kano model. The expected result of this research is to develop and to escalate the quality of service provided by Transvision, using SERVQUAL method and Kano model. This research identifies 26 attributes of customers needs based on interviews with loyal customers. SERVQUAL is used to measure customers satisfaction so that we can define the weak attributes of the attributes of needs. The result of data processing using SERVQUAL defines 18 weak attributes of the attribute of needs. Kano model is used to understand the relation between customers satisfaction and the means to achieve it. The result of data processing using Kano model defines 6 attributes categorized as a must-be attribute, 10 attributes as one dimensional, and 10 attributes as attractive. Based on SERVQUAL and Kano model integration resulting 20 attributes of customers needs which become the priorities to develop further. Keywords: Analysis of needs, SERVQUAL, Kano Model, Transvision.